Entrepreneurial strategies of Etna wine farms. (1st January 2014) - Tudisca, Salvatore; Di Trapani, Anna Maria; Donia, Enrica; Sgroi, Filippo; Testa, Riccardo
Viticulture, as well as agriculture in general, performs an environmental and landscaping function and it encourages rural development through the creation of income and job opportunities in the areas where wine is produced. The wine sector, in fact, is of great social and economic importance within the Sicilian agriculture and food industry, because of the job opportunities it provides and due to Sicilian pedoclimatic peculiarities, variety of grape wines cultivars and production process. The present study aims at assessing the competitiveness of small and medium-sized enterprises that cultivate wine grapes in the Etna area. In particular, it has been examined a sample of wine farms that produce Etna wine controlled designation of origin (DOC), a product with high value added, in order to assess their strategies adopted to compete in an increasingly wide and globalised market.